Sobre las calidades y qualidades de los indios americanos. Claves para comprender la limitación del derecho de representación en las Cortes Constituyentes de Cádiz (1812) - Martínez Almira, María Magdalena (2019)
The purpose of this paper is to analyze the terminology with which Indian people was identified, through a selection of sources for the knowledge of Indian law, amongst them legislation, documents relating to the implementation of law, memorials and reports submitted to the Spanish king. These are concepts loaded with legal significance, often with pejorative connotations that undervalued the capacities and competences of the Indigenous population. The limitation of rights, and in particular privileges and exemptions reserved to the Spaniards, could have its cause in this fact. The importance of the assignment of certain adjectives and names constantly in the genesis of the Indian citizen’s imaginary is evidenced in the process of building an American policy and, especially, in the Spanish constitutional process in the early nineteenth century.